2010
DOI: 10.1002/eji.201040983
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsic B‐cell defect supports autoimmunity in New Zealand black chromosome 13 congenic mice

Abstract: Introgression of a New Zealand Black (NZB) chromosome 13 interval onto a C57BL/6 (B6) background (B6.NZBc13) is sufficient to produce many hallmarks of lupus, including hightitre anti-chromatin antibody production, abnormal B-and T-cell activation, and renal disease. In this study we sought to characterize the immune defects leading to these abnormalities. By generating hematopoietic chimeras and BCR transgenic mice, we show that the congenic autoimmune phenotype can be transferred by BM cells and requires the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Other studies also suggest that MZ B cells are enriched for autoreactive clones compared to FO B cells (Cyster et al , 1994;Martin and Kearney, 2000). Chromosome 13 transgenic mice show skewing of splenic B cell subpopulations similar to our BrTg mice and also produce autoantibodies (Loh et al , 2011). However, the BrTg mice did not show altered surface activation markers as was found in the congenic mice.…”
Section: Discussionsupporting
confidence: 52%
“…Other studies also suggest that MZ B cells are enriched for autoreactive clones compared to FO B cells (Cyster et al , 1994;Martin and Kearney, 2000). Chromosome 13 transgenic mice show skewing of splenic B cell subpopulations similar to our BrTg mice and also produce autoantibodies (Loh et al , 2011). However, the BrTg mice did not show altered surface activation markers as was found in the congenic mice.…”
Section: Discussionsupporting
confidence: 52%
“…The only model that has been closely examined for TLR3 is the MRL.lpr, where TLR3 deficiency did not ameliorate disease, but this model is dominated by DNA autoantibodies (52). On the other hand, B cells containing a genetic susceptibility locus from the New Zealand Black autoimmune prone strain are hyperresponsive to TLR3 ligands (53). A better understanding of the role played by TLR7 and TLR3 in murine models and in patients will be useful when paired with autoantibody profiles to identify which TLR pathways are most relevant as therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of congenic mouse strains with introgressed homozygous intervals derived from lupus-prone mouse strains have provided considerable insight into how susceptibility loci promote disease development, less is known regarding the mechanisms involved in inhibition of autoimmunity by suppressor loci. Our laboratory has previously shown that introgression of a New Zealand Black (NZB) homozygous chromosome (c) 4 interval (B6.NZBc4), spanning 32-150 Mb, onto a C57BL/6 (B6) congenic mouse strain with a homozygous NZB c1 interval (B6.NZBc1) significantly attenuated the fatal autoimmunity observed in this mouse strain (B6.NZBc1c4), 1,2 indicating the presence of a suppressor locus on NZB c4. 3 Examination of the immune system in B6.NZBc4 mice revealed expansion of two innate-like lymphocyte populations, invariant Natural Killer T (NKT) cells and CD5 + B cells, leading us to hypothesize that one or both of these populations inhibit autoimmunity in B6.NZBc1c4 bicongenic mice.…”
Section: Introductionmentioning
confidence: 99%